Gambaran Tingkat Pengetahuan Akseptor KB dengan Pemilihan Metode Kontrasepsi Jangka Panjang di Wilayah Kerja Puskesmas Madurejo - Naimah Hakipsah; Sholaikhah Sulistyoningtyas (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The Indonesian government initiated the Family Planning Program to enhance the welfare of the population, given the high prevalence of couples of reproductive age (CRA). However, the coverage of family planning participants remains at only 57.4% of the total CRA. This research aims to provide an overview of the knowledge levels among family planning acceptors regarding the selection of long-term contraceptive methods (LTCMs) in the working area of Madurejo Health Center. Using a quantitative descriptive approach through a survey method, this study describes the knowledge levels and characteristics of LTCM selection among Madurejo Health Center's clients. The research involved a total of 60 respondents, categorized into LTCM acceptors and non-acceptors. The results indicate that the majority of respondents are aged between 21 and 35 years (46.7%), highly educated (90%), employed (78.3%), and possess a high economic status (63.3%). The most commonly chosen contraceptive methods are implants (28.3%) and IUDs (13.3%). Approximately 58.3% of respondents fall into the category of having moderate knowledge. In conclusion, the majority of family planning acceptors in the Madurejo Health Center area are individuals of reproductive age, with higher education, employment, high economic status, and moderate knowledge of long-term contraceptive methods. It is essential to continually enhance the knowledge and understanding of respondents in selecting suitable contraceptive methods.